The distribution of talent across contests - Ghazala Azmat; Marc Möller (Queen Mary University of London, School of Economics and Finance, 2016)
Do the contests with the largest prizes attract the most-able contestants? To what extent do contestants avoid competition? In this paper, we show, theoretically and empirically, that the distribution of abilities plays a crucial role in determining contest choice. Complete sorting exists only when the proportion of high-ability contestants is sufficiently small. As this proportion increases, high-ability contestants shy away from competition and sorting decreases, such that, reverse sorting becomes a possibility. We test our theoretical predictions with a large panel data set containing contest choice over twenty years. We use exogenous variation in the participation of highly-able competitors to provide empirical evidence for the relationship among prizes, competition, and sorting.
Keywords: L20; M52; D02; 330; Contests; Competition; Sorting; Incentives